2021
DOI: 10.1152/jn.00331.2020
|View full text |Cite
|
Sign up to set email alerts
|

Small dendritic synapses enhance temporal coding in a model of cochlear nucleus bushy cells

Abstract: Spherical bushy cells (SBCs) in the the anteroventral cochlear nucleus receive a single or very few powerful axosomatic inputs from the auditory nerve. However, SBCs are also contacted by small regular bouton synapses of the auditory nerve, located in their dendritic tree. The function of these small inputs is unknown. It was speculated that the interaction of axosomatic inputs with small dendritic inputs improved temporal precision, but direct evidence for this is missing. In a compartment model of spherical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Supporting the generality of these observations across stimuli, improved temporal precision in the coincidence and mixed modes is also mirrored when using a different measure, the shuffled correlation index, for transient stimuli. Our results are also consistent with simulations showing that small ANF synapses on dendrites can improve temporal precision in the presence of large somatic inputs ( Koert and Kuenzel, 2021 ). The simulations may also help explain the experimental cross-correlation results between ANFs and BCs of Young and Sachs ( 2008 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Supporting the generality of these observations across stimuli, improved temporal precision in the coincidence and mixed modes is also mirrored when using a different measure, the shuffled correlation index, for transient stimuli. Our results are also consistent with simulations showing that small ANF synapses on dendrites can improve temporal precision in the presence of large somatic inputs ( Koert and Kuenzel, 2021 ). The simulations may also help explain the experimental cross-correlation results between ANFs and BCs of Young and Sachs ( 2008 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this report, we add pipelines from neuron reconstruction to biophysically-inspired compartmental models of multiple cells. These models expand on previous BC models that used qualitative arguments, or single or double (soma, dendrite) compartments ( Joris et al,1994b , a; Rothman et al,1993 ; Rothman and Manis,2003c ; Spirou et al,2005 ; Koert and Kuenzel,2021 ). By matching inputs to a cochlear model ( Zilany et al,2014 ; Rudnicki et al,2015 ), we created a wellconstrained data exploration framework that expands on previous work ( Manis and Campagnola, 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…5A). These dendritic synapses are probably not a major source of excitatory drive to elicit spikes in bushy neurons, especially after considering the fact that dendritic signals are substantially attenuated due to the cable property of the dendrites (White et al, 1994; Sumner et al, 2009; Koert and Kuenzel, 2021). Besides the excitatory AN synapses, inhibitory synapses were also found on the dendrites (Gomez-Nieto and Rubio, 2009, 2011; Spirou et al, 2022), which help provide modulatory inhibition to regulate discharge rate and temporal precision of bushy neurons (Caspary et al, 1994; Kopp-Scheinpflug et al, 2002; Gai and Carney, 2008; Xie and Manis, 2013; Kuenzel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, these dendritic synapses are small in size and not the main driving force to trigger spikes in bushy neurons. Nevertheless, they help modulate the efficacy of the main inputs on the soma and improve the temporal precision and fidelity of encoded information in bushy neurons (Koert and Kuenzel, 2021). Given the functional significance of SGNs with medium/low spontaneous rate in coding loud sounds (Liberman, 1978), the findings suggest that bushy cell dendrites may play unique roles in encoding specific auditory signals, especially in noisy environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these small contacts modulate auditory processing by improving the temporal precision and fidelity. 33 Other cell types can be found in the VNC such as the T-stellate cells that project out of the CN to numerous targets in the brainstem but also form contacts within the CN. T-stellate cells exhibit several different functions and thus encode a wide spectrum of sound.…”
Section: Introductionmentioning
confidence: 99%